2022
DOI: 10.3389/fonc.2022.799930
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Effect of Radiotherapy on Stage IIB/III Pancreatic Cancer Undergone Surgery in Different Age and Tumor Site Groups: A Propensity Scores Matching Analysis Based on SEER Database

Abstract: BackgroundIt remains controversial whether radiotherapy (RT) improves survival in patients with stage IIB/III PDAC. A growing number of studies have found that patients’ age at diagnosis and tumor site not only affect prognosis, but also may lead to different treatment responses. Therefore, the purpose of this study was to verify whether the survival effect of radiotherapy in patients with stage IIB/III PDAC varies across age and tumor site groups.MethodsThe target population was selected from PDAC patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Circulating tumour cells that enter peripheral blood are thought to contribute to metastatic disease with worse survival [ 77 ]. In an analysis of the Surveillance, Epidemiology, and End Results database, patients with PDAC with a tumour location over the pancreatic head, stage II/III cancer, T4 cancer, N1 cancer, regional resection, or lymphadenectomy of ≥ 4 lymph nodes were demonstrated to benefit from adjuvant radiotherapy [ 78 , 79 ]. Several studies have revealed that a combined analysis of radiomic features, clinical parameters, pathology score, and tissue/serum biomarkers improves the prognostic power of clinical outcomes in PDAC [ 32 , 80 ].…”
Section: Potential Biomarkers For Identifying Patients With Pdac Suit...mentioning
confidence: 99%
“…Circulating tumour cells that enter peripheral blood are thought to contribute to metastatic disease with worse survival [ 77 ]. In an analysis of the Surveillance, Epidemiology, and End Results database, patients with PDAC with a tumour location over the pancreatic head, stage II/III cancer, T4 cancer, N1 cancer, regional resection, or lymphadenectomy of ≥ 4 lymph nodes were demonstrated to benefit from adjuvant radiotherapy [ 78 , 79 ]. Several studies have revealed that a combined analysis of radiomic features, clinical parameters, pathology score, and tissue/serum biomarkers improves the prognostic power of clinical outcomes in PDAC [ 32 , 80 ].…”
Section: Potential Biomarkers For Identifying Patients With Pdac Suit...mentioning
confidence: 99%
“…Nonetheless, the latest data did not support that increasing RT in young patients improved prognosis or had greater survival benefit than in older patients. However, young people can undergo more extensive surgery and chemoradiotherapy [ 78 , 79 ]. Health conditions such as frailty may be more closely associated with radiation toxicity.…”
Section: The Role Of Senescence In Types Of Pancreatic Diseasesmentioning
confidence: 99%
“…Patients were grouped by year of diagnosis (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) for demographic and clinical characteristics, including race, age, gender, marital status, tumor grade (I, II, III/IV), summary stage (localized, regional, distant) and treatment information (surgery and chemotherapy). With reference to previous studies, Grade III and Grade IV were reclassified into one category for the analysis [9,10]. Localized stage means that the tumor is confined to the appendix (T1-3) and there is no metastasis to lymph nodes or other organs or tissues.…”
Section: Patient Selectionmentioning
confidence: 99%